Revitalizing the Madrasah Brand: A Strategic Roadmap for Enhancing Quality and Fortifying Image - Muhammad Fathul Amin; Najiburrahman Najiburrahman; Ahmad Muzakki Hakim (Journal of Educational Management Research, 2023)
This study aims to investigate efforts to improve brand image in Madrasah Diniyah Nurul Jadid through perceived quality by considering improving the quality of education, transparency and accountability, facilities and infrastructure, quality of teachers and staff, and student achievement. This research method is qualitative research with a case study approach, which involves in-depth interviews with various related parties in Madrasah Diniyah Nurul Jadid. The results showed that Madrasah Diniyah Nurul Jadid has made various efforts in improving its brand image through perceived quality. Improving the quality of education, carried out by improving the curriculum and presenting qualified, experienced, and highly dedicated teachers in the learning process. Transparency and accountability, in all aspects of Madrasah life. Facilities and infrastructure, in Madrasah Diniyah Nurul Jadid have also been well considered. Quality teachers and staff, Teachers and staff at Madrasah diniyah Nurul Jadid have played an active role in creating a positive learning environment. Student achievement, students of Madrasah diniyah Nurul Jadid managed to achieve achievements in various fields. Continuous efforts in improving these aspects have formed a positive image of Madrasah Diniyah Nurul Jadid as an educational institution that is superior, dignified, and committed to producing quality next generations.